Private Net Benefits from Afforesting Marginal Cropland and Shrubland with Cork Oaks in Spain - Ovando, Paola; Campos, Pablo; Oviedo, José L.; Montero, Gregorio (Forest Science, 2010)
We estimate the private net benefits from afforesting marginal shrubland and cropland with cork oaks at two Spanish cork oak sites, Aljibe and Gavarres, in different time horizon frames. The analysis integrates market and nonmarket (landowner amenity) private capital incomes, including government afforestation grants. We apply cost-benefit analysis techniques for estimating the investment present value in the periods analyzed, taking residual values of cork oak woodland into account. The results show that the profitability rate of cork oak afforestation strongly depends on government subsidies. The value of private amenities, at least in Aljibe, seems to be positively affected by the forest area's share of the total estate surface. Thus, an increase in the afforested area would enhance the private amenity annual income with respect to maintaining the original property land's treeless uses. A higher level of private amenities attached to the forest area may imply a reduction in government grants for encouraging cork oak afforestation.
Keywords: cost-benefit analysis; government grants; market incomes; private amenity

Contingent Valuation of Woodland-Owner Private Amenities in Spain, Portugal, and California. - Campos, Pablo; Oviedo, José L.; Caparros, Alejandro; Huntsinger, Lynn; Coelho, Inocencio (Rangeland Ecology & Management, 2009)
Most of the Mediterranean woodlands in Spain, Portugal, and California are managed as agrosilvopastoral enterprises, producing some combination of livestock, wood, cork products, and crops, as well as wildlife habitat and diverse environmental services. Private amenity benefits to landowners have been suggested as an explanation for high land prices and the persistence of such rangeland enterprises despite apparently marginal cash returns. In this study, private amenity values are estimated using a contingent valuation technique in surveys of private woodland owners as part of five case studies, using a design developed to separate landowner amenity income and capital values. Nonindustrial private landowners were asked about the maximum amount of money that they were willing to give up (to pay) before selling their property to invest in more commercially profitable assets, and the proportion of the market price of their woodland that they think is explained by privately consumed amenities. Amenity values were found to be relevant because, in all cases, landowners were willing to pay > €120 · ha−1 · yr−1, at 2002 prices, and attributed > 30% of land market price to amenities. These values represent an amenity profitability rate > 2% in all case studies. The data analysis shows some similarities, but mostly divergences, in the different land-simulated and amenity-simulated markets.
Keywords: agroforestry systems; environmental economics; environmental services; Mediterranean woodlands; private ownership; Stated Preferences

Contingent Valuation of Woodland-Owner Private Amenities in Spain, Portugal, and California. - Campos, Pablo; Oviedo, Jose L; Caparros, Alejandro; Huntsinger, Lynn; Coelho, Inocencio (Rangeland Ecology & Management, 2009)
Most of the Mediterranean woodlands in Spain, Portugal, and California are managed as agrosilvopastoral enterprises, producing some combination of livestock, wood, cork products, and crops, as well as wildlife habitat and diverse environmental services. Private amenity benefits to landowners have been suggested as an explanation for high land prices and the persistence of such rangeland enterprises despite apparently marginal cash returns. In this study, private amenity values are estimated using a contingent valuation technique in surveys of private woodland owners as part of five case studies, using a design developed to separate landowner amenity income and capital values. Nonindustrial private landowners were asked about the maximum amount of money that they were willing to give up (to pay) before selling their property to invest in more commercially profitable assets, and the proportion of the market price of their woodland that they think is explained by privately consumed amenities. Amenity values were found to be relevant because, in all cases, landowners were willing to pay >€120 · ha−1 · yr−1, at 2002 prices, and attributed > 30% of land market price to amenities. These values represent an amenity profitability rate > 2% in all case studies. The data analysis shows some similarities, but mostly divergences, in the different land-simulated and amenity-simulated markets.
Keywords: agroforestry systems; environmental economics; environmental services; Mediterranean woodlands; private ownership; Stated Preferences

Accounting for single and aggregated forest incomes: Application to public cork oak forests in Jerez (Spain) and Iteimia (Tunisia) - Campos, Pablo; Daly-Hassen, Hamed; Oviedo, Jose L; Ovando, Paola; Chebil, Ali (Ecological Economics, 2008)
This study presents an applied improvement in the agroforestry accounting system (AAS) approach to two public cork oak forests in the Mediterranean region: Jerez (Spain) and Iteimia (Tunisia). Both forests have similar environments but differ in land property rights, labour markets and countries (developed and developing economy, respectively). The income analysis considers the differences between forest ownership, and household and landowner economic rationalities. In the case of Jerez, the public landowner has a right to exclude others from using the forest resources; community employment and natural resource conservation criteria determine Jerez's management. In the Iteimia case, the public landowner has regulated free-use rights for livestock grazing, firewood and crops so that local households can meet their needs and improve their income. Households operate by maximizing their income from the full employment of their own family workforce. The results show that Jerez's management generates negative commercial capital income for the public landowner, despite receiving significant public subsidies, while it maintains high internal forestry investment that generates additional local employment. Conversely, Iteimia produces positive commercial capital income for the public landowner and high household self-employed labour income per hectare.
Keywords: Agroforestry accounting system; Cork Oak Forest; Household economic rationality; Public ownership; Total commercial income

Does private income support sustainable agroforestry in Spanish dehesa? - Campos, Pablo; Ovando, Paola; Montero, Gregorio (Land Use Policy, 2008)
Oak woodland dehesa suffers from the aging of trees without a natural regeneration of young oaks coming in to replace them. Recent European Union (EU) policy reforms for rural development focus on supporting multifunctional agriculture that complies with the EU’s environmental goals, such as mitigating biodiversity losses and climate change. Such reforms could result in government support for natural woodland regeneration practices in European agroforestry systems, which are recognized for providing valuable environmental services. Managing dehesa cork oak and holm oak woodlands to stimulate the growth of new oaks could be an efficient option for maintaining, and even increasing, the dehesa’s current carbon stock and biodiversity. Here we develop and apply a new agroforestry accounting system based on the concept of Hicksian income to a dehesa in the Monfragu¨ e area of western Spain, using primary microeconomic data from a large case study. Private total income and profitability rates are measured for individual goods and services, and for the entire dehesa in a steady state. Our application extends the EU system of accounts for agriculture and forestry by including private amenity consumption by landowners and the gain or loss in human-made and natural capital. We compare an actual typical unsustainable woodland management scenario with an ideal sustainable management scenario in which there is a continuous regeneration and recruitment of holm and cork oaks as predicted by silvicultural models. The results show that, given current land use policy incentives, allowing a slow depletion of oak trees is more profitable for a dehesa private landowner than maintaining the dehesa’s trees. As a result many dehesa environmental services are gradually lost. This market failure requires new land use policies that induce private land owners to invest in the renewal of aging oak woodlands. To evaluate the impacts of this new policy, we show how private landowner income is affected when changes are made to achieve sustainable management of dehesa oaks. More research is needed in order to understand how the dehesa’s landowner market income and private amenities trade-off can affect the owner’s land use preferences and decisions.
Keywords: Amenities; environmental services; Monte; Oak silviculture; Rural development policy; Total income

Does private income support sustainable agroforestry in Spanish dehesa? - Campos, Pablo; Ovando, Paola; Montero, Gregorio (Land Use Policy, 2008)
Oak woodland dehesa suffers from the aging of trees without a natural regeneration of young oaks coming in to replace them. Recent European Union (EU) policy reforms for rural development focus on supporting multifunctional agriculture that complies with the EU’s environmental goals, such as mitigating biodiversity losses and climate change. Such reforms could result in government support for natural woodland regeneration practices in European agroforestry systems, which are recognized for providing valuable environmental services. Managing dehesa cork oak and holm oak woodlands to stimulate the growth of new oaks could be an efficient option for maintaining, and even increasing, the dehesa’s current carbon stock and biodiversity. Here we develop and apply a new agroforestry accounting system based on the concept of Hicksian income to a dehesa in the Monfragu¨ e area of western Spain, using primary microeconomic data from a large case study. Private total income and profitability rates are measured for individual goods and services, and for the entire dehesa in a steady state. Our application extends the EU system of accounts for agriculture and forestry by including private amenity consumption by landowners and the gain or loss in human-made and natural capital. We compare an actual typical unsustainable woodland management scenario with an ideal sustainable management scenario in which there is a continuous regeneration and recruitment of holm and cork oaks as predicted by silvicultural models. The results show that, given current land use policy incentives, allowing a slow depletion of oak trees is more profitable for a dehesa private landowner than maintaining the dehesa’s trees. As a result many dehesa environmental services are gradually lost. This market failure requires new land use policies that induce private land owners to invest in the renewal of aging oak woodlands. To evaluate the impacts of this new policy, we show how private landowner income is affected when changes are made to achieve sustainable management of dehesa oaks. More research is needed in order to understand how the dehesa’s landowner market income and private amenities trade-off can affect the owner’s land use preferences and decisions.
Keywords: Amenities; environmental services; Monte; Oak silviculture; Rural development policy; Total income

Would you choose your preferred option? Comparing choice and recoded ranking experiments - Caparros, Alejandro; Oviedo, Jose L; Campos, Pablo (AMERICAN JOURNAL OF AGRICULTURAL ECONOMICS, 2008)
Previous research has shown that results from a choice experiment are statistically different from those obtained from a ranking experiment that is recoded and treated as a choice experiment using only the first rank. By avoiding some of the shortcomings of previous comparisons, we obtain the opposite results using data from the valuation of a cork oak reforestation program in the south of Spain. Structural models and welfare estimations are statistically indistinguishable irrespective of the use of parametric or bootstrapping tests. Further, we employ follow-up questions and subsample analysis to test whether divergences appear when potential effects are isolated.
Keywords: choice modeling; conjoint analysis; cork oak reforestation; environmental preferences; recoded ranking

Forestaciones con encina y alcornoque en el área de la dehesa en el marco del - Ovando, Paola; Campos, Pablo; Montero, Gregorio (Revista Española de estudios agrosociales y pesqueros, 2007)
La Unión Europea adopta en el año 1992 una serie de medidas de acompañamiento a la reforma de la política agraria común. La política de abandono de tierras agrícolas dedicadas a cultivos excedentarios fue incentivada mediante ayudas a su forestación, reguladas por el Reglamento 2080/1992. Esta intervención pública ha tenido en el área de la dehesa española una influencia favorable a la expansión de sus dos especies forestales más emblemáticas: la encina (Quercus ilex) y el alcornoque (Quercus suber ). La superficie forestada con encina y alcornoque entre 1993 y 2000 supera las 281.000 hectáreas en las comunidades autónomas de Andalucía, Castilla-La Mancha, Castilla y León, Extremadura y Madrid, que concentran alrededor del 95 por ciento de la superficie forestada con ambas especies en España. Este estudio tiene como objetivo ofrecer un análisis descriptivo de los efectos de las forestaciones con encina y alcornoque en los cambios de usos del suelo, así como la influencia que ha tenido la distribución del gasto público en las Comunidades Autónomas del área de la dehesa, en aplicación del Reglamento (CE) 2080/1992.
Keywords: alcornoque (PG); cambio de uso; Dehesa; encina; forestación de tierras agrarias

Forestaciones con encina y alcornoque en el área de la dehesa en el marco del - Ovando, Paola; Campos, Pablo; Montero, Gregorio (Revista Española de estudios agrosociales y pesqueros, 2007)
La Unión Europea adopta en el año 1992 una serie de medidas de acompañamiento a la reforma de la política agraria común. La política de abandono de tierras agrícolas dedicadas a cultivos excedentarios fue incentivada mediante ayudas a su forestación, reguladas por el Reglamento 2080/1992. Esta intervención pública ha tenido en el área de la dehesa española una influencia favorable a la expansión de sus dos especies forestales más emblemáticas: la encina (Quercus ilex) y el alcornoque (Quercus suber ). La superficie forestada con encina y alcornoque entre 1993 y 2000 supera las 281.000 hectáreas en las comunidades autónomas de Andalucía, Castilla-La Mancha, Castilla y León, Extremadura y Madrid, que concentran alrededor del 95 por ciento de la superficie forestada con ambas especies en España. Este estudio tiene como objetivo ofrecer un análisis descriptivo de los efectos de las forestaciones con encina y alcornoque en los cambios de usos del suelo, así como la influencia que ha tenido la distribución del gasto público en las Comunidades Autónomas del área de la dehesa, en aplicación del Reglamento (CE) 2080/1992.
Keywords: alcornoque (PG); cambio de uso; Dehesa; encina; forestación de tierras agrarias

Measuring total sustainable incomes from multifunctional management of Corsican Maritime Pine and Andalusian Cork oak Mediterranean forests - Campos, Pablo; Bonnieux, François; Caparros, Alejandro; Paoli, Jean-Christophe (Journal of Environmental Planning and Management, 2007)
Abstract Enough advances have recently been made in income accounting theory to recommend that environmental services accruing either to the forest owner or to the general public should be included in the forest accounting system. In this study, the results of two case studies, one in Bonifatu, Corsica (France) and the other in Alcornocales, Andalusia (Spain), show that private environmental services provide the majority share of social total sustainable income in Alcornocales (29%), whereas public environmental services are the most relevant in Bonifatu (32%). The social total sustainable income measured by the agroforestry accounting system is, respectively, 1.6 and 2.4 times higher than the income estimated by economic accounts for forestry in Alcornocales and Bonifatu forests.
doi: 10.1080/09640560601048424
Keywords: accounting system; benefits; Bonifatu; environmental services; Los Alcornocales; management (voyant); market price; sustainable income; Values

Measuring total sustainable incomes from multifunctional management of Corsican Maritime Pine and Andalusian Cork oak Mediterranean forests - Campos, Pablo; Bonnieux, François; Caparros, Alejandro; Paoli, Jean-Christophe (Journal of Environmental Planning and Management, 2007)
Abstract Enough advances have recently been made in income accounting theory to recommend that environmental services accruing either to the forest owner or to the general public should be included in the forest accounting system. In this study, the results of two case studies, one in Bonifatu, Corsica (France) and the other in Alcornocales, Andalusia (Spain), show that private environmental services provide the majority share of social total sustainable income in Alcornocales (29%), whereas public environmental services are the most relevant in Bonifatu (32%). The social total sustainable income measured by the agroforestry accounting system is, respectively, 1.6 and 2.4 times higher than the income estimated by economic accounts for forestry in Alcornocales and Bonifatu forests.
doi: 10.1080/09640560601048424doi: 10.1080/09640560601048424The following values have no corresponding Zotero field: publisher: Routledge
Keywords: accounting system; benefits; Bonifatu; environmental services; Los Alcornocales; management (voyant); market price; sustainable income; Values

Modeling Multifunctional Agroforestry Systems with Environmental Values: Dehesa in Spain and Woodland Ranches in California - Campos, Pablo; Caparros, Alejandro; Cerdá, Emilio (Handbook Of Operations Research In Natural Resources, 2007)
The high environmental and amenity values of Mediterranean oak woodlands influence the response of the public and landowners to market forces and to public policies for the management of oak woodland areas. In California and in Spain, woodlands with a Quercus overstory open enough to allow the development of a significant grassy or shrubby understory harbor exceptional levels of biodiversity, provide watershed and habitat, sequester carbon, offer historically meaningful landscapes, and are pleasing to the eye. For historic reasons, and because of the social and environmental values of the woodlands for their owners, large private holdings based on sylvopastoral enterprises have and will have a crucial role in the future of the woodlands. Simple financial models for predicting landowner behavior based on response to market forces do not explain landowner retention of oaks without incorporation of landowner consumption of environmental and amenity values from the property, because landowner utility for oaks is not fully accounted for. By the same token, predicting the best afforestation approach considering carbon sequestration alone without consideration of the biodiversity and amenity values of native oaks risks an overvaluation of planting alien species that could have negative environmental and social consequences. Reforestation models for carbon sequestration that do not incorporate biodiversity and public amenity values might favor plantings of alien species such as eucalyptus; however, this does not take into account the high public and private consumption values of native oaks.
The following values have no corresponding Zotero field: periodical: Handbook Of Operations Research In Natural Resources electronic-resource-num: 10.1007/978-0-387-71815-6
Keywords: Carbon Sequestration; Firewood; Oak woodlands; Optimal Control; optimization model

Modeling Multifunctional Agroforestry Systems with Environmental Values: Dehesa in Spain and Woodland Ranches in California - Campos, Pablo; Caparros, Alejandro; Cerdá, Emilio (Handbook Of Operations Research In Natural Resources, 2007)
The high environmental and amenity values of Mediterranean oak woodlands influence the response of the public and landowners to market forces and to public policies for the management of oak woodland areas. In California and in Spain, woodlands with a Quercus overstory open enough to allow the development of a significant grassy or shrubby understory harbor exceptional levels of biodiversity, provide watershed and habitat, sequester carbon, offer historically meaningful landscapes, and are pleasing to the eye. For historic reasons, and because of the social and environmental values of the woodlands for their owners, large private holdings based on sylvopastoral enterprises have and will have a crucial role in the future of the woodlands. Simple financial models for predicting landowner behavior based on response to market forces do not explain landowner retention of oaks without incorporation of landowner consumption of environmental and amenity values from the property, because landowner utility for oaks is not fully accounted for. By the same token, predicting the best afforestation approach considering carbon sequestration alone without consideration of the biodiversity and amenity values of native oaks risks an overvaluation of planting alien species that could have negative environmental and social consequences. Reforestation models for carbon sequestration that do not incorporate biodiversity and public amenity values might favor plantings of alien species such as eucalyptus; however, this does not take into account the high public and private consumption values of native oaks.
Keywords: Carbon Sequestration; Firewood; Oak woodlands; Optimal Control; optimization model